Distinct Metabolic Signals Underlie Clone by Environment Interplay in “Nebbiolo” Grapes Over Ripening - Pagliarani, Chiara; Boccacci, Paolo; Chitarra, Walter; Cosentino, Emanuela; Sandri, Marco; Perrone, Irene; Mori, Alessia; Cuozzo, Danila; Nerva, Luca; Rossato, Marzia; Zuccolotto, Paola; Pezzotti, Mario; et al. (Frontiers in Plant Science, 2019)
Several research studies were focused to understand how grapevine cultivars respond to environment, nevertheless the biological mechanisms tuning this phenomenon need to be further deepened. Particularly, the molecular processes underlying the interplay between clones of the same cultivar and environment were poorly investigated. To address this issue, we analyzed the transcriptome of berries from three ‘Nebbiolo’ clones grown in different vineyards, during two ripening seasons. RNA-sequencing data were implemented with analyses of candidate genes, secondary metabolites, and agronomical parameters. This multidisciplinary approach helped to dissect the complexity of clone x environment interactions, by identifying the molecular responses controlled by genotype, vineyard, phenological phase or a combination of these factors. Transcripts associated to sugar signalling, anthocyanin biosynthesis and transport were differently modulated among clones, according to changes in berry agronomical features. Conversely, genes involved in defense response, such as stilbene synthase genes, were significantly affected by vineyard, consistently with stilbenoid accumulation. Thus, besides at the cultivar level, clone-specific molecular responses also contribute to shape the agronomic features of grapes in different environments. This reveals a further level of complexity in the regulation of genotype x environment interactions that has to be considered for orienting viticultural practices aimed at enhancing the quality of grape productions.